2020
DOI: 10.1111/jocd.13531
|View full text |Cite
|
Sign up to set email alerts
|

Why we should be avoiding periorificial mimetic muscles when injecting tissue fillers

Abstract: Background Tissue fillers are generally safe and well tolerated by patients. However, complications do occur and may be very severe, such as intravascular injection (with occasional residual tissue loss, visual and neurological sequelae) and late nodularity and swelling. Methods to lessen the likelihood of complications have been the subject of much recent literature. Depth of injection has been identified as a key safety consideration. Patients/Methods The role of injection of facial filler into the muscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…In cadaver studies, vertical needle placement has been shown to allow filler in many layers, 17 including the dangerous muscular lamella. 23 This may be due to the bevel length, which reaches up to 2 mm for a 25-gauge needle (down to 1 mm for 30 gauge). This may allow filler to be deposited not only at the tip but also along the entire length of the bevel and with retrograde flow up the track left by the passage of the needle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cadaver studies, vertical needle placement has been shown to allow filler in many layers, 17 including the dangerous muscular lamella. 23 This may be due to the bevel length, which reaches up to 2 mm for a 25-gauge needle (down to 1 mm for 30 gauge). This may allow filler to be deposited not only at the tip but also along the entire length of the bevel and with retrograde flow up the track left by the passage of the needle.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, deep injections on bone are considered safer practice in the mid-face, deep pyriform space, and temple because deep injections bypass the middle lamella where mimetic or masticatory muscles and major vessels are found. 23 However, foramina are found in the supraperiosteal plane in the mid-face. Cadaver studies have highlighted the relevance of these issues.…”
Section: Resultsmentioning
confidence: 99%
“…Injection in the mimetic muscles, especially the sphincteric muscles, should be avoided to minimize the risk of complications. 66 …”
Section: Discussionmentioning
confidence: 99%
“…4 There is also an inherent risk of injury or paralysis to the frontal branches of the facial nerve when injecting into this region, which may lead to temporary brow ptosis. Goodman et al 174 recommend avoiding injecting into mimetic muscular layers, as this may produce product clumping, displacement, and tendency for late nodularity swelling. 174 A safe injection zone has been previously outlined by Tansatit et al 38 as the intersection of the temporal and the frontal processes of the zygomatic bone at the posterior angle of the zygoma.…”
Section: Avoidance Of Vascular Adverse Eventsmentioning
confidence: 99%
“…Goodman et al 174 recommend avoiding injecting into mimetic muscular layers, as this may produce product clumping, displacement, and tendency for late nodularity swelling. 174 A safe injection zone has been previously outlined by Tansatit et al 38 as the intersection of the temporal and the frontal processes of the zygomatic bone at the posterior angle of the zygoma. The maximum depression of the temporal region that is undergoing correction typically resides in this area, allowing it to serve as a landmark for safe injection.…”
Section: Avoidance Of Vascular Adverse Eventsmentioning
confidence: 99%